New furoxan derivatives for the treatment of ocular hypertension. Issue 3 (1st February 2017) - Blangetti, Marco; Rolando, Barbara; Chegaev, Konstantin; Guglielmo, Stefano; Lazzarato, Loretta; Durante, Mariaconcetta; Masini, Emanuela; Almirante, Nicoletta; Bastia, Elena; Impagnatiello, Francesco; Fruttero, Roberta; Gasco, Alberto
Graphical abstract: Abstract: A small series of water-soluble NO-donor furoxans bearing a basic center at the 4-position, having a wide lipophilic-hydrophilic balance range, and endowed with different NO-release capacities, were synthesized and characterized. Selected members were studied for their IOP-lowering activity in the transient ocular hypertensive rabbit model at 1% dose. The most effective IOP-lowering products were compounds3 and7, whose activity 60 min after administration was similar to that of Timolol. Notably, 7 was characterized by a long-lasting action. The IOP-lowering activity in this series of products appeared to be modulated by the lipophilic-hydrophilic balance rather than by the NO-donor capacity.